The Distribution and Influence Factors of Non-Invasive Tear Film Break-Up Time in Children [Letter] - Rani A; Yadav RK (Clinical Ophthalmology)
Anjali Rani, Rakesh Kumar Yadav Department of Optometry, Teerthanker Mahaveer University, Moradabad, UP, IndiaCorrespondence: Anjali Rani, Department of Optometry, College of Paramedical Sciences, Teerthanker Mahaveer University, NH-09, Delhi road Bagadpur, Moradabad, UP, 244001, India, Email optomanjali1997@gmail.com